Bargaining with evolving private information - Juan Ortner (Theoretical Economics, 2023)
I study how the arrival of new private information affects bargaining outcomes. A seller makes offers to a buyer. The buyer is privately informed about her valuation, and the seller privately observes her stochastically changing cost of delivering the good. Prices fall gradually at the early stages of negotiations, and trade is inefficiently delayed. The first-best is implementable via a mechanism, whereas all equilibrium outcomes of the bargaining game are inefficient.
Keywords: C73; C78; D42; D82; 330; Bargaining; Coase conjecture; evolving private information; inefficient delay; two-sided private information